The effect of psychological well-being and self-esteem on loneliness of migrant students in Medan - Simarmata, Nenny Ika Putri; Parsaulian Aritonang, Nancy Naomi Gabe; Simanullang, Rapina; Sitanggang, Roulina (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
The purpose of this study was to determine the effect of psychological well-being and self-esteem on loneliness of migrant students. The researchers used a quantitative approach, involving 108 migrant students in Medan, who were selected through a purposive sampling technique. Data collection in the study used the Ryff's psychological well-being scale, Rosenberg self-esteem scale (RSES), and the loneliness scale according to Peplau and Perlman. Analysis of research data used multiple linear regression techniques. Based on the simultaneous significance test result of 0.000>0.005, it means that self- esteem and psychological well-being simultaneously have a negative effect on loneliness, meaning that the higher the psychological well-being, the lower the level of loneliness. Conversely, loneliness will increase if psychological well-being decreases. The researchers found that 16% of the loneliness variable can be explained by psychological well-being and self-esteem, which shows a significant contribution of both variables in reducing feelings of loneliness in individuals.